Simulation Analysis of a Power System Protection using Artificial Neural Network - Aejaz Ahmed K R; Mohd. Z. A. Ansari; Mohamed Jalaluddin (International Journal of Electrical and Computer Engineering (IJECE), 2013)
There has been significant development in the area of neural network based power system protection in the previous decade. Neural network technology has been applied for various protective relaying functions including distance protection. The aim of this Paper is to develop a software module acting as a protective relay using neural network techniques. The Artificial Neural Network (ANN) software developed module employs the back-propagation method to recognize the waveform patterns of impedance in a transmission line. The input waveforms are generated using PSCAD. The generated waveforms then are used as training and testing data for the ANN software. The ANN software is simulated using the Neural Network Toolbox. The design has been tested for different fault conditions including different fault resistances and fault inception angles. The test results show that the relay is able to detect faults in lesser time as compared to conventional relay algorithms.DOI:http://dx.doi.org/10.11591/ijece.v3i1.1938